Medicinal Gingival Hyperplasia Associated with the Use of Risperidone in Childhood: Clinical Case Report (Global Journal of Medical Research, 2022)
Medicated gingival hyperplasia is an exaggerated increase in gingival tissue, having been reported in patients treated with anticonvulsant and antipsychotic drugs, usually associated with the presence of plaque, gingival inflammation and genetic predisposition, a condition considered as one of the factors that can provide aesthetic results unfavorable and harm periodontal health. As gingival therapy, there is gingivectomy surgery, which tends to considerably resolve the condition of hyperplasia, especially if it is associated with the control of bacterial plaque, through adequate oral hygiene.
Keywords: gingivectomy gingival hyperplasia risperidone